Decoding the multifaceted interventions between human sirtuin 2 and dynamic hepatitis B viral proteins to confirm their roles in HBV replication - Piracha, Zahra Zahid; Saeed, Umar; Piracha, Irfan Ellahi; Noor, Seneen; Noor, Elyeen (Frontiers in Cellular and Infection Microbiology, 2024)
Human SIRT2, encoding the full-length Sirt2 protein (Sirt2 isoform 1), primarily functions as a cytoplasmic α-tubulin deacetylase and plays a significant role in promoting the growth of hepatocellular carcinoma (HCC). The intricate interplay between HBV replication and Sirt2 is multifaceted: HBV replication, either independently or through HBx-mediated transcriptional transactivation, enhances Sirt2.1 expression, and reciprocally, Sirt2.1 positively elevates HBV transcription and replication. Sirt2.1's association with liver fibrosis and epithelial-to-mesenchymal transition escalates the risk of HCC. Mechanistically, Sirt2.1 activates the AKT/GSK3β/β-catenin pathway, fostering the HBV replication cycle. Additionally, it stimulates the transcription of viral enhancer I/HBx promoter (EnI/Xp) and enhancer II/HBc promoter (EnII/Cp) by targeting the transcription factor p53. Sirt2 isoform 2 (Sirt2.2), primarily localized in the cytoplasm, exhibits a truncated N-terminal region, yet retains the ability to moderately enhance HBV replication and activate the AKT/GSK3β/β-catenin signaling pathway. In contrast, Sirt2 isoform 5 (Sirt2.5), primarily located in the nucleus, lacks a nuclear export signal (NES) and features a truncated catalytic domain (CD). Despite these alterations, Sirt2.5 tends to protect the cell from HBV-induced damage or death by implementing regulatory mechanisms that impede viral mRNAs, HBc, core particles, replicative intermediate (RI) DNAs, and covalently closed circular DNA (cccDNA) levels, thereby limiting HBV replication. Intriguingly, Sirt2.5-mediated HBV replication operates independently of the AKT/GSK3β/β-catenin signaling cascade. Upon HBV replication, the expression of Sirt2 isoforms is heightened, contributing to a self-sustaining cycle of viral replication and disease progression. Sirt2.5, in particular, exhibits unique characteristics. It is recruited more prominently to cccDNA than Sirt2.1, resulting in the deposition of additional histone lysine methyltransferases (HKMTs), including SETDB1, SUV39H1, EZH2, and PR-Set7, along with corresponding transcriptional repressive markers like H3K9me3, H3K27me3, and H4K20me1 onto HBV cccDNA. In HBV replicating cells, Sirt2.5 forms complexes with PR-Set7 and SETDB1, further influencing transcriptional regulation. Importantly, Sirt2.5 has the capability to inhibit transcription from cccDNA through epigenetic modifications, achieved via direct or indirect interactions with HKMTs. This intricate network underscores the nuanced regulatory roles of different Sirt2 isoforms in the complex landscape of HBV replication and its impact on host cell survival.